Design, development and evaluation of furrow opener for differential depth fertilizer application - SINGH, K P; AGRAWAL, K N; JAT, DILIP; KUMAR, MANISH; KUSHWAHA, H L; SHRIVASTAVA, PRATEEK; TRIPATHI, HIMANSHU (The Indian Journal of Agricultural Sciences, 2016)
A differential depth furrow opener for tractor-drawn seed-cum-fertilizer drill under raised beds sowing was designed, developed and evaluated at ICAR-Central Institute of Agricultural Engineering, Bhopal, MP, India. The basic aim of this development was to apply fertilizer at different depth in crop root zone to enhance the fertilizer use efficiency. The furrow opener was evaluated based on draught and power requirements under soil bin at four depths (5, 10, 15, and 20 cm), four forward speeds (1.8, 3.2, 4.3 and 5.4 km/h) and three compaction level (200, 400 and 600 kPa). The field performance evaluation of furrow opener was done in two wheat crop varieties; HI-1544 (Triticum aestivum L.) and HI-8663 (T. durum) under raised beds. The experiment consisted of different fertilizer placement depths, i.e. application of NPK mixed fertilizer on surface (T1) and 5 cm (T2), 10 cm (T3), 15 cm (T4) and 20 cm (T5) below the surface in split-plot design. The root weight/plant shows significant results under all treatments, maximum and minimum root weight/plant were observed 16.01 and 9.63 g in T3 and T5, respectively. Highest grain yield was observed in treatment T4 (6 048 kg/ha) followed by T3 (5 611), T2 (5 223), T1 (4 739) and T5 (4 493 kg/ha). Higher NDVI values were observed in T3 (0.95) and T4 (0.96) at heading stage of wheat crop. From crop attributes point of view, parallel results were observed for T3 (10 cm) and T4 (15cm). But considering the draught and power requirement, 15 cm deep fertilization required 47% and 42% higher draught and power, respectively as compared to 10 cm deep fertilization.